Potencial utilización de la termografía infrarroja para la lectura de la IDTB en cabras - Pérez de Diego Camacho, A. C.; Ortega Martín, C.; Domínguez Rodríguez , L.; Sánchez-vizcaíno Rodríguez, J. M. (Revista Complutense de Ciencias Veterinarias, 2008)
The aim of this experiment is to study the potential use of IT (infrared termography) for measurement of PPD (Purified protein derivate) test in goats. The study of the temperatures showed a significant increase at 24hours post-inoculation of the PPD in the set of all the individuals, not being observed significant influence of the colour of the animals on the temperatures. The comparison of the results from the PPD skin test, and IT did not demonstrate significant association.